Prognostic value and early response stratification of a multi-biomarker panel in cervical cancer patients undergoing chemoradiotherapy - Wang, Yu; Gan, Na; Ning, Shan; Qiu, Yinting (Frontiers in Oncology, 2025)
AimsDespite progress in chemoradiotherapy (CRT), outcomes in cervical cancer still vary widely. Minimally invasive biomarkers may enable risk stratification and treatment optimization.MethodsWe prospectively enrolled 164 International Federation of Gynecology and Obstetrics (FIGO) IB–IVA patients, all receiving CRT plus brachytherapy. Baseline blood markers and HPV subtypes were assessed. Treatment response was evaluated at three months, and progression-free (PFS) and overall survival (OS) were measured over a median of 36 months.ResultsElevated squamous cell carcinoma antigen (SCC-Ag), Cancer antigen 125 (CA125), Interleukin-6 (IL-6), C-reactive protein (CRP), and high neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio (NLR/PLR) correlated with advanced disease. At three months, 87.1% showed complete response (CR) or partial response (PR). Higher IL-6, CRP, SCC-Ag, CA125, and NLR/PLR were linked to poorer response. At 36 months, PFS and OS were 65.2% and 74.5%, respectively. High-risk patients had lower PFS (58.1% vs. 72.4%) and OS (64.5% vs. 82.0%), independent of stage, with no increase in severe toxicity.ConclusionsA multi-biomarker panel shows superior discrimination for early response and is prognostic for survival in locally advanced cervical cancer. Larger, multi-institutional studies are warranted to validate this panel, standardize assays, and investigate additional markers or imaging-based strategies, ultimately facilitating more personalized therapy and improved outcomes. shows superior discrimination for early response and is prognostic for survival in locally advanced cervical cancer.